1999
DOI: 10.1063/1.873611
|View full text |Cite
|
Sign up to set email alerts
|

Energetic particle transport in compact quasi-axisymmetric stellarators

Abstract: Hamiltonian coordinate, guiding center code calculations of the confinement of suprathermal ions in quasi-axisymmetric stellarator (QAS) designs have been carried out to evaluate the atractiveness of compact configurations which are optimized for ballooning stability. A new stellarator particle following code is used to predict ion loss rates and particle confinement for thermal and neutral beam ions in a small experiment with R=145 cm, B= 1-2 T and for alpha particles in a reactor size device. In contrast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
1
14
1
Order By: Relevance
“…15 shows the time evolution of the fraction of beam ion loss in one energy slowing down time for configuration P01/I00. The concave structure of the loss evolution with time is characteristic of QAS [19], and is unlike the convex time evolution plots more typically seen in tokamak beam ion orbit simulations [21,22]. Over time, more and more ions find their way into loss orbits in the QAS stellarator, while in tokamaks, the incremental losses decrease with time.…”
Section: Energetic Particle Transportmentioning
confidence: 87%
See 3 more Smart Citations
“…15 shows the time evolution of the fraction of beam ion loss in one energy slowing down time for configuration P01/I00. The concave structure of the loss evolution with time is characteristic of QAS [19], and is unlike the convex time evolution plots more typically seen in tokamak beam ion orbit simulations [21,22]. Over time, more and more ions find their way into loss orbits in the QAS stellarator, while in tokamaks, the incremental losses decrease with time.…”
Section: Energetic Particle Transportmentioning
confidence: 87%
“…We have recently shown that in QAS the thermal and energetic particle transport behavior are correlated [19], so that we expect these plasmas will also not differ greatly in their thermal ion confinement. While good transport and MHD stability are not anticorrelated in these thirty equilibria, stability only results from a delicate balance of the pressure and shear stabilization forces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the thermal confinement times, we have also calculated the energy losses of 40 keV H-neutral beam ions at B=2T using Monte Carlo simulations. 23,24 In addition to our physics targets, we have also compared candidate configurations with respect to two quantities that provide a measure of the attractiveness of the associated coils. For this purpose, a set of saddle coils has been constructed for each candidate configuration.…”
Section: Configuration Optimization Toolsmentioning
confidence: 99%